Achieving the millennium development goals : (Transport publishing house, 2007)
It documents the progress made in improving the health of women and their babies abd UNFPA's role in the successes to date.It also points towards the directly and inrextly ipact on maternal and child health. This document identifies valuable lesson for the plainning and application of future maternal and newborn health progrsmmes by government, NGOs.